Peran Sosial Mahasiswa melalui Kegiatan Berbagi Sembako dan Perlengkapan Sekolah dalam Mendukung Kesejahteraan Masyarakat Sidoarjo - Didit Darmawan; Alvina Safitri; Rahayu Mardikaningsih; Fayola Issalillah; Rafadi Khan Khayru (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Community well-being is a crucial indicator of social development. However, segments of the population still face limitations in meeting basic needs, particularly regarding food and education. Addressing this situation requires contributions from various stakeholders, including university students through Community Service (PkM) activities. This initiative aimed to implement a food and school supply distribution program based on the Asset-Based Community Development (ABCD) framework and to assess its impact on community well-being and student character development in Sidoarjo Regency. The study employed the ABCD approach combined with SWOT analysis to identify strengths, weaknesses, opportunities, and threats during program implementation. The activity stages included identifying community needs, mobilizing resources, distributing aid, and evaluating the program's execution. Results indicate that food and school supplies were successfully distributed to the target community in accordance with previously identified needs. The program received a positive response from the community, as it helped meet families' basic needs and supported the continuity of education for children from underprivileged households. Beyond providing social and economic benefits to recipients, the activity fostered empathy, social concern, and a sense of responsibility among students regarding community issues. Thus, the implementation of an ABCD-based aid distribution program serves as an effective form of community service that supports community well-being while simultaneously strengthening students' social character.